Relationship between Employment Status and Knowledge of Balanced Nutrition with Nutritional Status Students - Marhamah, Marhamah; Emilia, Esi; Yusrafiddin, Yusrafiddin; Pakpahan, Sondang P; Rassy, Regania Pasca (Nutrition Study Program, Faculty of Medicine, Universitas Negeri Semarang, Indonesia, 2023)
The Open University is one of the campuses of choice for students who work while studying. Limited time due to busy work causes nutritional problems. The purpose of the study was to determine the relationship between employment status and balanced nutrition knowledge with the nutritional status of Open University students. Cross-sectional research design with respondents totaling 84 people. The study was conducted from November to December 2022. Data collection using google form. The data is processed with the SPSS program and presented in descriptive form and correlation tests. The relationship between variables is analyzed with the Spearman Test. A total of 73.8% of respondents were employed and 26.2% were unemployed. The average nutritional knowledge of respondents was 68.78%. Half of the respondents had normal nutritional status, 38% overnutrition status and 11.4% undernourished. The results of the study did not have a relationship between employment status and nutritional status but there was a positive relationship between nutritional knowledge and nutritional status. The value of the correlation coefficient between the variables of occupational status and balanced nutrition knowledge is 0.312, which shows that there is a positive correlation and relationship between employment status and nutritional knowledge with nutritional status.